Scalp Melanoma Diagnosed by Fine Needle Aspiration Cytology in a Tertiary Health Center - A. B. Zarami; N. A. Satumari; M. Ahmed (Case Reports in Oncological Medicine)
Melanoma is one of the most aggressive malignant skin neoplasms worldwide with more than 20% of world melanoma seen in black Africa and Asia. Late presentation due to ignorance, poverty, and lack of adequate health facility in Nigeria is always the norms. We present this case report because of precision in diagnosis, using fine needle aspiration cytology (FNAC) to reemphasize that the technique is cheap, cost effective, and quick that can reduce the burden of incisional biopsy before definitive surgery and improve early detection of the disease especially in developing countries.